A method for measuring mitochondrial DNA copy number in pediatric populations - Maggo, Simran; North, Liam Y.; Ozuna, Aime; Ostrow, Dejerianne; Grajeda, Yander R.; Hakimjavadi, Hesamedin; Cotter, Jennifer A.; Judkins, Alexander R.; Levitt, Pat; Gai, Xiaowu (Frontiers in Pediatrics, 2024)
The mitochondrion is a multifunctional organelle that modulates multiple systems critical for homeostasis during pathophysiological stress. Variation in mitochondrial DNA (mtDNA) copy number (mtDNAcn), a key mitochondrial change associated with chronic stress, is an emerging biomarker for disease pathology and progression. mtDNAcn can be quantified from whole blood samples using qPCR to determine the ratio of mtDNA to nuclear DNA. However, the collection of blood samples in pediatric populations, particularly in infants and young children, can be technically challenging, yield much smaller volume samples, and can be distressing for the patients and their caregivers. Therefore, we have validated a mtDNAcn assay utilizing DNA from simple buccal swabs (Isohelix SK-2S) and report here it's performance in specimens from infants (age = <12 months).Utilizing qPCR to amplify ~200bp regions from two mitochondrial (ND1, ND6) and two nuclear (BECN1, NEB) genes, we demonstrated absolute (100%) concordance with results from low-pass whole genome sequencing (lpWGS). We believe that this method overcomes key obstacles to measuring mtDNAcn in pediatric populations and creates the possibility for development of clinical assays to measure mitochondrial change during pathophysiological stress.